Land Dispossession In Poems Tribal Birth by Margaret Armstrong (1998), We Are Of A Tribe by Alberto Rios (2017), and Mother Earth by Nola Gregory (2020) - Yeni, Resfida; Al-Hafizh, Muhd. (English Language and Literature, 2023)
This research is an analysis of the poems Tribal Birth by Margaret Armstrong (1998), We Are of A Tribe by Alberto Rios (2017), and Mother Earth by Nola Gregory (2020). In this study, the author aims to reveal the form of land dispossession and the effort in protecting the land faced by the Aborigines in Australia. In this analysis, there are two forms of land dispossesion as an part of Aborigine. The first is colonial domination by the white people in order to taking the land. The second is indigenous rights as Aborigines. This analysis uses Post - Colonial theory to reveal the forms and the effort in protecting the land by the Aborigines. The use of concept based on the context of the poems and the interpretation of the text. In this analysis, the element of poetry that help reveal the implied meaning are tone, speaker, repetition and symbol.